COMMUNITARIAN DIMENSION OF SOCIAL INTEGRITY PROBLEM - Yuliia Yu. Brodetskaya (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose. The article focuses on the study analysis of the theoretical and methodological preconditions of the social integrity phenomenon research. The nature of the modern social and cultural changes discloses a crisis of the social theory that is aimed to study the conditions and mechanisms of the social modernity development. Modern social theory appears against the background of the classical research methodology issues – Aristotle's political philosophy, which interprets sociality as a political aspect. However, modern social theory attempts to overcome the crisis of the rational project by forming a communitarians’ ideology. In order to solve the problem of the social integrity and order, being an alternative to the rationalistic individualism of society liberal theory, the theory of communitarism reveals the potential of communities. The communities are those models of social that can overcome individualism of a modern man and society, destroy the cult of statism. Thus, as a research methodology of the social integrity issues the communitarian approach is used, as it actualizes the potential of the communities. This methodological step reveals the social at a qualitatively different socio-cultural level of analysis, as a certain model of the human relations that base not only on the economic and legal relations (relations, property, division of labor and power, etc.), but also, and above all, on the spiritual ones (culture of community, communication, informal regulation of relations, etc.). The scientific novelty of this work is to try to expand the heuristic possibilities of the com munitarian theory in terms of the analysis of the social integrity problems in order to create a comprehensive research methodology of the problem. Conclusions. Thus, the study of the community potential, its mechanisms and the logic of its generation and presentation in the modern society allows to reveal the conditions of the social integrity. Therefore, it will allow to overcome the problem of the social crisis, which is stated by the modern researchers.